Blended learning in higher education : framework, principles, and guidelines - Garrison, D. R. (D. Randy), 1945-; Vaughan, Norman D., 1960- (San Francisco : Jossey-Bass, 2008)
'This groundbreaking book offers a down-to-earth resource for the practical application of blended learning in higher education as well as a comprehensive examination of the topic. Well-grounded in research, Blended Learning in Higher Education demonstrates how the blended learning approach embraces the traditional values of face-to-face teaching and integrates the best practices of online learning. This approach has proven to both enhance and expand the effectiveness and efficiency of teaching and learning in higher education across disciplines.'--BOOK JACKET.
Includes bibliographical references (p. 223-231) and index.
Keywords: Education, Higher -- Computer-assisted instruction; Blended learning; Internet in higher education